Kesiapan dan Persepsi Masyarakat Kabupaten Bondowoso terhadap Kebijakan Jaminan Kesehatan Nasional (JKN) (Preparedness and Perception of Bondowoso Community for National Health Insurance) - Eri Witcahyo (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Bondowoso is districts in East Java with the third lowest HDI, which amounted to 65.39 with a lifeexpectancy of 63.95 years. It shows that access to health is still limited. According to theseconditions, it needs for a review the implementation of the National Health Insurance policy. Theobjective of this study was to analyze the preparedness and perception of Bondowosocommunity for the National Health Insurance (NHI) policy. This type of research is observationaldescriptive with quantitative approach. The sample was 192 respondents with multistage randomsampling technique. Data was obtained through interviews using a questionnaire, and thenanalyzed using univariate and presented descriptively. Research shows that respondents aged40-49 years (39.1%), male sex (68.8%) with a high school education level / equivalent (55.2%).Resources owned television (97.4%). However, respondents get information NHI fromneighbors / friends (54.1%), respondents felt the need to have health insurance for families(65.6%). There were 58.3% of respondents who were not participants NHI the groundscomplexity procedures (46.4%). Income and expenditure of respondents in the range of1,000,000 to 2,000,000 rupiah. NHI amounts of fees that could be accepted by the response was5,000 rupiah (31.8%).Keywords: preparedness, perception, national health insurance